ORGANIZATIONS AND ACTIVITIES OF HIGHER EDUCATIONAL INSTITUTIONS OF UKRAINE DURING THE ANTI-TERRORIST OPERATION - Korolov, Yurii; Korolov, Vasyl (Актуальні проблеми правознавства, 2025)
Analyzing the events and crises that are taking place in schools and universities around the world, an important question arises: do educational institutions in Ukraine, in addition to changes in organization, programs and legislation, pay enough attention to ensuring and strengthening the safety of children and youth? This is especially relevant in connection with the emergence of new threats, such as terrorism. Studies show that Polish schools do not prepare children for the correct behavior in the event of a terrorist threat. The level of preparation depends on many factors, in particular, on the level of anti-terrorist awareness, which is formed thanks to effective educational work and state legislative activity [1]. In the article, the authors analyzed the current situation in the school system in the context of security, focusing on legal, educational and developmental aspects that need improvement. Particularly noteworthy are the European Convention on the Suppression of Terrorism of January 27, 1977, the International Convention for the Suppression of the Taking of Hostages of December 17, 1979, the International Convention for the Suppression of the Financing of Terrorism of December 9, 1999, the Council of Europe Convention on the Prevention of Terrorism of May 16, 2005, the Additional Protocol to the Council of Europe Convention on the Prevention of Terrorism. Signed by Ukraine on October 28, 2015. In this regard, a lot has been done in the field of legal support for countering terrorism in Ukraine. Thus, in the Criminal Code of Ukraine, adopted on April 5, 2001, in Article 258, responsibility for committing a terrorist act is established, and the Law of Ukraine of March 20, 2003 No. 638-IV «On Combating Terrorism» provides for the main organizational and legal means of countering terrorist manifestations. After the ratification of the Council of Europe Convention on the Prevention of Terrorism, the laws of Ukraine of September 21, 2006 No. 170-V and May 18, 2010 No. 2258-VI were adopted, which supplemented the Criminal Code of Ukraine with Articles 2581–2585, which provide for liability for involvement in the commission of a terrorist act (Article 2581 of the Criminal Code), public calls to commit a terrorist act (Article 2582 of the Criminal Code), creation of a terrorist group or terrorist organization (Article 2583 of the Criminal Code), assistance in the commission of a terrorist act (Article 2584 of the Criminal Code), financing of terrorism (Article 2585 of the Criminal Code)